MAKNA PERTUNJUKAN SENI CALUNG TARAWANGSA BAGI WARGA KABUPATEN TASIKMALAYA (STUDI FENOMENOLOGI) - Rusmawan Mawardi; Erman Anom (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2022)
ABSTRACTAlong with the development of today's era and technology, cultural arts rarely show their existence and millennials have forgotten about the existence of cultural arts and traditions in Indonesia. Although there are still some millennials who care about cultural arts and traditions, they do not understand the meaning of these cultural arts. In West Java, Tasikmalaya has a variety of cultures and traditions, especially  Tawarangsa, but today many Tasikmalaya millennials do not know the existence of these cultures and traditions. Of course, the researcher wants to preserve the existence and describe the implied meaning of  Tarawangsa. Then what is the meaning of the  Tarawangsa art performance in Tasikmalaya Regency? Using a phenomenological study approach, phenomenology is defined as natural phenomena, as well as events that can be felt and can be seen by the five senses, this gives the meaning that a phenomenon is something that can be seen, observed and interpreted as part of human life. The purpose of this study is to find out and understand further and in depth the meaning of the  Tarawangsa Art Performance for the residents of Tasikmalaya Regency and describe the meaning implied in the  Tarawangsa art performance. The method used in this research is a qualitative research method with a phenomenological approach to explain the meaning of  Tarawangsa art performances in Tasikmalaya Regency. Researchers conducted observations and interviews in Cangkuang village, Cikukulu Village, Karangnunggal District, Tasikmalaya Regency, West Java Province. Interviews were conducted with key informants and several informants from  Tarawangsa players and the surrounding community. From this study it can be concluded that the meaning of  Tarawangsa, this performance is carried out for the ritual of the ngala pare (rice harvest) event. By playing  Tarawangsa when the rice will be harvested and before the event is carried out, there is Mitamiyan/Mimitian (Starting) is an activity to mark with some rice stalks that are ready to be harvested in every corner of the rice fields. The whole series of rituals in the event of taking rice is accompanied by playing the art of  Tarawangsa. Keywords:  Tarawangsa, meaning, performing arts, phenomenology.